2024
DOI: 10.1186/s40798-024-00679-8
|View full text |Cite
|
Sign up to set email alerts
|

How Cool is That? The Effects of Menthol Mouth Rinsing on Exercise Capacity and Performance: A Systematic Review and Meta-analysis

Erica H. Gavel,
Gabriel Barreto,
Kierstyn V. Hawke
et al.

Abstract: Background Menthol (MEN) mouth rinsing (MR) has gained considerable interest in the athletic population for exercise performance; however, the overall magnitude of effect is unknown. Objective The aim of this systematic review and meta-analysis was to determine the efficacy of menthol MEN MR and the impact it has on exercise capacity and performance. Methods Three databases were searched with articles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This study demonstrated that there was not a significant difference in the cycling TT performance with a repeated MEN MR in thermoneutral conditions when MEN was combined with either CW or TNW. Although the results of this study are in contrast to research demonstrating the significant effect of MEN MR on cycling performance in hot conditions [6,11], the results are aligned with the one available paper investigating the effects of MEN MR in thermoneutral conditions [15] and a recent meta-analysis by Gavel et al [8] reported that there was no significant improvement in the vertical jump, isometric mid-thigh pull, or six-second sprint performance with the use of repeated MEN MR. In both the study by [15] and the current one, it is plausible that the overall stress of the thermoneutral environment and the MR stimulus (despite repeated MEN MR) may not have been strong enough to elicit a central effect leading to increased motor output and an acute increase in exercise performance [3].…”
Section: Influence Of Menthol Mouth Rinsing On Cycling Performancesupporting
confidence: 74%
See 4 more Smart Citations
“…This study demonstrated that there was not a significant difference in the cycling TT performance with a repeated MEN MR in thermoneutral conditions when MEN was combined with either CW or TNW. Although the results of this study are in contrast to research demonstrating the significant effect of MEN MR on cycling performance in hot conditions [6,11], the results are aligned with the one available paper investigating the effects of MEN MR in thermoneutral conditions [15] and a recent meta-analysis by Gavel et al [8] reported that there was no significant improvement in the vertical jump, isometric mid-thigh pull, or six-second sprint performance with the use of repeated MEN MR. In both the study by [15] and the current one, it is plausible that the overall stress of the thermoneutral environment and the MR stimulus (despite repeated MEN MR) may not have been strong enough to elicit a central effect leading to increased motor output and an acute increase in exercise performance [3].…”
Section: Influence Of Menthol Mouth Rinsing On Cycling Performancesupporting
confidence: 74%
“…This study demonstrated no performance improvement with the use of a MEN MR on strength and power exercises [15]. The effect of a MEN MR on endurance performance in a thermoneutral environment remains unknown [8]. Moreover, the synergistic effect of MEN MR and fluid temperature is also unknown.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations